Estimation of Serum Copper in Post-menopausal Women Attending in a Tertiary Care Hospital, Bangladesh (Anwer Khan Modern Medical College Journal, 2019)
Background: Nutritional needs change throughout the various stages of life. While overall caloric needs tend to decrease with age, the requirements for individual micronutrients do not decrease. In fact, the needs for some micronutrients actually increase with age. The risk of nutritional disturbances mainly trace elements deficiencies is high during postmenopause causing or intensifying serious clinical symptoms. Methods: This cross sectional study was carried out in the Department of Biochemistry, Mymensingh Medical College in collaboration with the Department of Obstetrics and Gynecology, Mymensingh Medical College Hospital during the period from July 2013 to June 2014. A total of 100 subjects were included in this study. Among them 50 apperantly healthy postmenopausal women (Case) aged between 45-60 years were considered as case and another 50 regular menstruating premenopausal women(Control) aged between 30-40 years were selected as control. Results: The mean age of cases and control groups was 50.5±2.3 years and 36.5±4.4 years respectively. In this study we found Serum Copper levels in cases and controls were 115.36±8.836 µg /dl and 90.58 ±6.315 µg/dl respectively had (p< 0.01) significant difference. Conclusion: Serum Copper level was significantly increased in postmenopausal group in comparison to premenopausal women (p< 0.01). Estimation of serum Cu level might be incorporated in every postmenopausal woman for prevention of complications.Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 110-113